MORAL VALUES IN T.S. ARTHUR’S SHORT STORY AN ANGEL IN DISGUISE - Meldy ocfendy Possumah; Ceisy Wuntu; Fivy Andries (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this research is To find out the moral values in T.S. Arthur’s Short Story An Angel in Disguise. This research is qualitative research since the data are collected from the primary source in the short story Angel in Disguise and the secondary source are books and the references that can be support this research. In analyzing the research the researcher uses objective approach that focused the internal elements of this short story as plot, characters, setting and so on. The results of the research shows moral values such as: Caring and responsible to children, Sympathetic to everyone who needs it, Empathy is needed to save someone life, life need patience, Be kind-hearted by giving hand to others and The power of love.